2015
DOI: 10.1021/acs.joc.5b02014
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoseletive Transannular Oxa-Conjugate Addition Generates the 2,6-cis-Disubstituted Tetrahydropyran of Neopeltolide

Abstract: Transannular 2,6-disubstituted pyrans, like the one found in the cytotoxic marine natural product neopeltolide, are a key functional group in many polyketides. While oxa-conjugate additions have been shown to provide direct and rapid access to tetrahydropyrans in acyclic neopeltolide intermediates, a transannular strategy for construction of this ring system in a macrocyclic core has not been investigated. In this study, we demonstrate that a transannular oxa-conjugate addition strategy is a viable approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Florence and Cadou reported their synthetic studies on neopeltolide, in which a transannular oxa-Michael reaction was planned as a key transformation [ 157 ]. Very recently, Boddy et al reported the synthesis of a neopeltolide model compound by using a transannular oxa-Michael addition [ 158 ].…”
Section: Synthesis Of Tetrahydropyrans Via Intramolecular Oxa-michmentioning
confidence: 99%
“…Florence and Cadou reported their synthetic studies on neopeltolide, in which a transannular oxa-Michael reaction was planned as a key transformation [ 157 ]. Very recently, Boddy et al reported the synthesis of a neopeltolide model compound by using a transannular oxa-Michael addition [ 158 ].…”
Section: Synthesis Of Tetrahydropyrans Via Intramolecular Oxa-michmentioning
confidence: 99%
“…Ring-closing metathesis was applied to the synthesis of 3,6-dihydro-2H-pyrans starting from diene and enyne skeletons using Grubbs catalysts (16TA954,16EJO3900) and also to construct the 5,6-dihydropyran-2-one ring in many natural compounds including cryptocaryol (16AGE5049), cryptomoscatone D1 and (5R,7S)-kurzilactone (16TL1087), the C1-C27 subunit of hemicalide (16JOC11275), 12 withanolide analogs (16S48), and in the synthesis of eight pure stereoisomers of pironetin-dumetorine hybrids, a new scaffold for tubulin binders (16EJO2029). Prins cyclization was used to build the tetrahydropyran core of four diarylheptanoids from Dioscorea villosa (16TL3505), while oxa-Michael cyclization reactions were used to prepare the tetrahydropyran rings of (−)-gilbertine (16JOC4566), neopeltolide (16JOC415), rhopaloic acid A (16AGE3455), and fragments of various polyketides (16AGE6280).…”
Section: Introductionmentioning
confidence: 99%